How to Face Uncertainty in Phosphorus Abatement Decisions in Water Management - Brabec, Jan; Vojáček, Ondřej, 1980-; Zajíček, Miroslav, 1975-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2016)
Implementation of EU Water Framework Directive has led to an increased demand for cost-benefit analysis in water management. The directive introduces a good status, which is required on all water bodies by 2027. Excessive phosphorus inflows are one of the main reasons for not meeting the criteria in the Czech Republic. If achieving of the good status is not cost-proportionate, exemption can be applied. Many different methodologies were created across different states, including Czech official methodology by Slavíková et al. (2015). However, this methodology does not deal with uncertainty of measures effectiveness. This thesis describes how to implement the uncertainty into calculations using Bayesian networks. A case study of Stanovice water reservoir demonstrates the approach practically. Results of the Bayesian network show, that selected measures with available data eliminate desired amount of phosphorus in 70% of all cases. This reduction is most likely sufficient, because it holds for the upper estimate of required abatement (60 to 200 kg). Based on comparison of benefits and costs, it seems net benefits are generated by implementing suggested measures. Therefore, policy recommendation is to implement the selected measures.
Vedoucí práce: Ondřej Vojáček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses